2020
DOI: 10.1097/jcn.0000000000000727
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Experiences of Transition From Hospital to Home After Their Infant's First-Stage Cardiac Surgery

Abstract: The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRaP URL' above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…Three studies conducted focus group interviews [40][41][42], one study analysed journal entries [43], and the remainder conducted interviews. Two studies were mixed methods, including a quantitative arm with self-reported psychometric testing [44,45]. One study triangulated their findings by assessing audio recordings of participant medical consultations [34].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies conducted focus group interviews [40][41][42], one study analysed journal entries [43], and the remainder conducted interviews. Two studies were mixed methods, including a quantitative arm with self-reported psychometric testing [44,45]. One study triangulated their findings by assessing audio recordings of participant medical consultations [34].…”
Section: Resultsmentioning
confidence: 99%
“…One study triangulated their findings by assessing audio recordings of participant medical consultations [34]. Four studies had longitudinal data [42,[45][46][47], with two studies reporting on components of larger studies [42,47]. Eighteen articles gathered cross-sectional information.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations